Real Sample Covid-19 Detection from Total RNA Screening by Using Biosensor - N. Dayana Mahazir; N. A. Parmin; Adilah Ayoib; M. A. Farehanim; NFM Nasir; N. Fareezah Jaapar; F. Syakirah Halim; Uda Hashim; Subash C. B. Gopinath; M. N. A. Uda; et al. (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
The rapid and accurate detection of COVID-19 is essential for effective disease management and control. This study presents the development of a Carbon Quantum Dot (CQD)-modified interdigitated electrode (IDE) biosensor for detecting COVID-19 RNA from total RNA extracted from real samples. The sensor exhibits a strong linear response across a wide concentration range, with a calculated limit of detection (LOD) of 6.534 x 10-6 µM. This sensitivity represents at least one order-of-magnitude improvement over previously reported systems, which typically achieve detection limits in the micromolar range. The enhanced detection capability is attributed to efficient electron transfer and signal amplification at 1 V, facilitated by the nanomaterial-modified electrode surface. Specificity was confirmed through successful discrimination of single-base mismatched and non-complementary RNA sequences, while reproducibility was validated by de-hybridization of RNA targets with retention of immobilized DNA probes. Signal interactions and amplification were analyzed using the Keithley 2450 Electrical Measurements Test, showing strong correlation with target RNA presence. Clinical validation using Reverse Transcription Polymerase Chain Reaction (RT-PCR) demonstrated 98% detection accuracy, underscoring the biosensor’s reliability. These findings highlight the CQD-IDE biosensor as a rapid, cost-effective, and robust diagnostic platform, offering a valuable alternative to conventional methods in enhancing COVID-19 detection capabilities.